The Ricks of Biomechanical Demands of Lifeguard Workers - Virginis, José Antonio (2024)
The protagonist of this work is a lifeguard worker who works in an aquatic environment, whose primary function is the prevention of accidents within the area of his responsibility. Firstly, the context, the most salient characteristics of the profession, the conceptual definitions, and the security elements will be explained. Secondly, the so-called risks of biomechanical demand and their main characteristics will be pointed out. Thirdly, the conclusions and different solution proposals introduced in a basic guide to good practices will be postulated.